Advertisement Remove all ads

Solve: ("9x" + 7)/2 - ("X" - ("X" - 2)/7) = 36 - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads
Sum

Solve: `("9x" + 7)/2 - ("x" - ("x" - 2)/7) = 36`

Advertisement Remove all ads

Solution

`("9x" + 7)/2 - ("x" - ("x" - 2)/7) = 36`


`=> ("9x" + 7)/2 - ((7 xx x - 1("x" - 2))/7) = 36`


`=> ("9x" + 7)/2 - ((7"x" - "x" - 2)/7) = 36`


`=> ("9x" + 7)/2 - (("6x" - 2)/7) = 36`


`=> (7(9"x" + 7) + 2(-6"x" + 2))/14 = 36`


`=> (63"x" + 49 - "12x" + 4)/14 = 36`


`=> ("51x" + 53)/14 = 36`

⇒ 51x + 53 = 14 × 36

⇒ 51x = 504 - 53

⇒ 51x = 459

⇒ x = `459/51`

∴ x = 9

Concept: Solving Linear Inequations
  Is there an error in this question or solution?

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 14 Linear Equations in one Variable
Exercise 14 (C) | Q 1.13 | Page 170
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×